Bioinspired superwettable electrodes towards electrochemical biosensing. Issue 18 (14th April 2022) - Zhu, Qinglin; Yang, Yuemeng; Gao, Hongxiao; Xu, Li-Ping; Wang, Shutao
Abstract : The recent progress of superhydrophilic/phobic electrodes, superaerophilic/phobic electrodes, superwettable patterned electrodes, Janus wettability electrodes and wettability switchable electrodes in electrochemical biosensing is reviewed. Abstract : Superwettable materials have attracted much attention due to their fascinating properties and great promise in several fields. Recently, superwettable materials have injected new vitality into electrochemical biosensors. Superwettable electrodes exhibit unique advantages, including large electrochemical active areas, electrochemical dynamics acceleration, and optimized management of mass transfer. In this review, the electrochemical reaction process at electrode/electrolyte interfaces and some fundamental understanding of superwettable materials are discussed. Then progress in different electrodes has been summarized, including superhydrophilic, superhydrophobic, superaerophilic, superaerophobic, and superwettable micropatterned electrodes, electrodes with switchable wettabilities, and electrodes with Janus wettabilities. Moreover, we also discussed the development of superwettable materials for wearable electrochemical sensors. Finally, our perspective for future research is presented.